Responsible investment and responsible consumption - Hendrik Hakenes; Eva Schliephake (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
To reduce a negative externality, socially responsible households can invest responsibly (SRI), consume responsibly (SRC), or do both. Which is better? In a closed microeconomic model with intertwined product and capital markets, we analyze how responsible households should use SRI and SRC to maximize their impact. Both strategies reduce the externality as long as investors are risk-averse and the products have no perfect substitutes. Responsible households gain the highest impact when using SRC in equal proportion to SRI. A mere focus on SRC is never efficient. SRI plays a role in any green strategy. The financial performance of green investments is determined by the responsible households' mix between SRI and SRC.
Keywords: D16; G30; G23; D62; D64; M14; 330; Socially responsible investment (SRI); ethical investment; socially responsible consumption (SRC); sustainable investment; sustainable consumption; green investment; divestment; ESG; SPI